Political Party Activities and the Quagmire for Economic Development in Nigeria since the Resurgence of Democracy - Emmanuel Vembe; Thaddeus T. Ityonzughul; Idahosa Osagie Ojo (Covenant University Journal of Politics and International Affairs, 2023)
There is mushrooming literature on political party activities in Nigeria. However, existing research has not focused much on how political parties became an albatross to Nigeria's economy. As a result, this study adds to the body of literature on the phenomenon under inquiry. Using existing historical data and statistical information, it confirms the critical link between political party activities and economic decline in Nigeria. Given the foregoing, the study suggests, among other things, a cessation of election violence and excessive campaign financing, which are the "roadmaps" for Nigeria's economic decline. These and other related ideas, if examined and implemented, will assist the country in finding the correct path to inclusive growth and sustainable economic development rather than leaving it in ruins.